1994
DOI: 10.1002/apmc.1994.052210116
|View full text |Cite
|
Sign up to set email alerts
|

Triazine‐based polymers, 2. Synthesis and characterization of polyethers

Abstract: Triazine-based polyethers can be synthesized by phase transfer catalysed interfacial polycondensation at room temperature and reaction times of about 1 to 3 h. In this way, more than 20 polyethers were synthesized and solubilities, glass transition temperatures, thermogravimetric data, elongations at break, tensile strengths, elasticity moduli and impact strengths were determined. In addition, the degree of crystallinity was investigated for the polymer obtained from of 2,4-dichloro-6-diethylamino-s-triazine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…These data are in good agreement with those published by Braun and Ziser [11,20] for their poly(ethoxy-cyanurate)s which their obtained from the copolymerisation of 2,4-dichloro-6-ethoxy-s-triazine with a variety of bisphenols.…”
Section: Polymersupporting
confidence: 91%
See 1 more Smart Citation
“…These data are in good agreement with those published by Braun and Ziser [11,20] for their poly(ethoxy-cyanurate)s which their obtained from the copolymerisation of 2,4-dichloro-6-ethoxy-s-triazine with a variety of bisphenols.…”
Section: Polymersupporting
confidence: 91%
“…A number of workers have reported exotherms in poly(methoxycyanurate)s when subjected to similar heating cycles [10,13,14,[22][23][24]. However, it is interesting to note that Braun and Ziser [11,20], who worked extensively with 2,4-dichloro-6-ethoxy-triazine, did not report exothermic behaviour in their samples. On first inspection, the nature of the changes in the samples which gave rise to the prominent exotherms observed would appear to be due to crystallisation in the polymer matrix; TGA data showed clearly that there was no weight loss associated with the event.…”
Section: Investigation Into Crystallisation Behaviour Of Polycyanuratesmentioning
confidence: 87%
“…The exotherms are generally very similar for all the samples analysed in this work and also to other data reported by other workers for poly(methoxy-cyanurate)s subjected to similar heating cycles [6,9,10,20e22]. Although Braun and Ziser [8,17], who worked extensively with 2,4-dichloro-6-ethoxy-triazine, did not report exothermic behaviour in their samples, we have observed similar behaviour in poly(methoxy-cyanurate)s [4]. The exothermic peaks observed in the DSC thermograms were analysed using the method of Sun et al [23] on the assumption that a single first order process was responsible for the exotherm.…”
supporting
confidence: 88%
“…3. All the samples displayed similar stability in nitrogen and the onsets of decomposition were of comparable magnitude to those observed for poly(methoxy-cyanurate)s [4] and poly(ethoxy-cyanurate)s [8,17], with the primary differences being that the poly(methoxy-thiocyanurate)s exhibit a slightly higher char yield at 490 C (average char yield 62%). A dynamic TGA study of DPEMTC from ambient to 1000 C in nitrogen showed that decomposition proceeds via a three-stage mechanism.…”
mentioning
confidence: 64%
“…Polymers and supramolecules containing 1,3,5-triazine units have been widely used in industry [1][2][3][4][5][6][7] because of their high thermal stability. In recent years, some new types of polymers and supramolecules containing 1,3,5-triazine units have been reported.…”
Section: Introductionmentioning
confidence: 99%